Observing Nebulosities: The Cygnus Superbubble - Christopherson, Christopher; Kaltcheva, Nadia (Proceedings of the Wisconsin Space Conference, 2016)
The Galactic star-forming complexes are best delineated by the distribution of the ionized interstellar matter which is always associated with active star-formation. Observations of these regions at specific emission lines are helpful in determining the overall distribution of the interstellar gas and dust, and also tracing supernova shock fronts and regions of strong stellar winds. Amateur astrophotography equipment is often useful in obtaining homogeneous coverage of large-scale star-forming fields that in some cases does not yet exist as part of professional all-sky surveys. For this project we observe the Cygnus star-forming complex in the Hydrogen-Î±, Hydrogen-Î² and Oxygen-III emission lines. We use a computer-guided modified Digital Single Lens Reflex (DSLR) camera combined with a wide-angle lens to image a 22Â° x 17Â° field, including in this way all prominent star-formation sites in Cygnus.